Pengaruh Gaya Kepemimpinan terhadap Turnover Intention Karyawan Hotel GI di Denpasar Bali - Ni Desak Made Santi Diwyarthi; Anjani Jasmine Patria (Yayasan Literasi Sains Indonesia, 2024)
This study aims to analyze the influence of leadership style on employee turnover intensity at Hotel GI, Bali. The sample consisted of 47 respondents selected using stratified random sampling. This technique is appropriate due to the heterogeneous population with distinct subgroups, ensuring proportional representation. Data collection was conducted through questionnaires with a Likert scale. Leadership style was used as the independent variable and turnover intention as the dependent variable. Validity and reliability tests were carried out to ensure a robust research instrument (Cronbach's Alpha > 0.8). Simple linear regression analysis showed that leadership style has a significant negative effect on turnover intention (R = 62.5%). This means that the application of better leadership styles can reduce employees' desire to leave the organization. This research result is in line with the Leader-Member Exchange (LMX) theory which emphasizes the positive impact of a strong relationship between leaders and employees on job satisfaction and retention. This study also supports previous research on the role of transformational leadership in reducing turnover. It is recommended that leaders implement clear and directed leadership styles to minimize misunderstandings and improve employee retention..